The role of oxidative stress in corneal diseases and injuries - Čejková, Jitka; Čejka, Čestmír (Histology and histopathology, 2015)
In various corneal injuries (such as chemical burns or irradiation of corneas with UVB radiation) and ocular diseases (e.g. dry eye disease, keratokonus, bullous keratopathy, Fuchs' endothelial dystrophy), the expressions of malondialdehyde (a marker of lipid peroxidation) and nitrotyrosine (a marker of oxidative stress) appeared in cells of individual corneal layers and conjunctival cells (dry eye disease). This is in contrast to healthy corneas in which negligible levels of malondialdehyde and no expressions of nitrotyrosine are present. The injured or diseased corneas reveal decreased capacity of antioxidants (enzymatic as well as non-enzymatic), whereas the levels of pro-oxidants (e.g. oxidases that generate reactive oxygen species) remain at physiological levels or even increase, leading to the antioxidant/prooxidant imbalance and oxidative stress. Oxidative stress in the cornea stimulates generation of pro-inflammatory cytokines, proteolytic enzymes and enzymes that generate nitric oxide (nitric oxide synthases). An abundant amout of reactive oxygen species and nitric oxide lead to the formation of toxic reactive products contributing to tissue damage. This review aims to summarize immunohistochemical changes in severe corneal injuries and diseases in which oxidative stress has been proved.
Keywords: Corneal Diseases; Animals; Oxidative Stress; nemoci rohovky; Cornea; Radiation Injuries; malondialdehyd; lidé; Corneal Injuries; zvířata; radiační poranění; poranění rohovky; oxidační stres; Ultraviolet Rays; Malondialdehyde; rohovka; ultrafialové záření; Humans